2017
DOI: 10.1007/s13187-017-1205-8
|View full text |Cite
|
Sign up to set email alerts
|

Talking About Your Prostate: Perspectives from Providers and Community Members

Abstract: Prostate cancer (PrCA) screening is controversial, especially for African-American (AA) men who have higher PrCA incidence and mortality than other racial/ethnic groups. Patient-provider communication is important for the PrCA screening decision process. The study purpose was to better understand the current dialogue between primary care providers (PCPs—physicians and nurse practitioners) and AA men about PrCA prevention and screening. An online survey with 46 PCPs, education sessions (including pre/post surve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…The study of cancer communication among prostate cancer survivors has focused heavily on communication between the physician and the patient to identify barriers to prostate cancer screenings and prostate cancer knowledge (Choi et al, 2018;Pedersen et al, 2012;Woods-Burnham et al, 2018). Studies indicated minimal health communication regarding cancer and sexual function occurred among Black families (Friedman et al, 2012;Hovick et al, 2015;Thompson et al, 2015) due to lack of connection or closeness between family members, fear of gossip, stigmatization, and traditional views of health being a private topic (Bowen et al, 2017;Hovick et al, 2015;Thompson et al, 2015;.…”
Section: Cancer and Health Disclosure In Black Familiesmentioning
confidence: 99%
“…The study of cancer communication among prostate cancer survivors has focused heavily on communication between the physician and the patient to identify barriers to prostate cancer screenings and prostate cancer knowledge (Choi et al, 2018;Pedersen et al, 2012;Woods-Burnham et al, 2018). Studies indicated minimal health communication regarding cancer and sexual function occurred among Black families (Friedman et al, 2012;Hovick et al, 2015;Thompson et al, 2015) due to lack of connection or closeness between family members, fear of gossip, stigmatization, and traditional views of health being a private topic (Bowen et al, 2017;Hovick et al, 2015;Thompson et al, 2015;.…”
Section: Cancer and Health Disclosure In Black Familiesmentioning
confidence: 99%
“…Primary healthcare providers are the foremost cancer information resources for Black men [19][20][21][22]. Patient-provider communication about PSA screening is positively associated with PSA uptake.…”
Section: Discussionmentioning
confidence: 99%
“…The wide difference in the prevalence of screening among other states in the United States might also indicate the role providers' practice plays in the high prevalence of screening. Differences in provider types across geographic areas and urban and rural communities, 33 in organizations that most frequently influence providers' practices, 34,35 and in patients' preferences could contribute to varying screening use.…”
Section: Discussionmentioning
confidence: 99%